2013
DOI: 10.1007/s11255-013-0407-1
|View full text |Cite
|
Sign up to set email alerts
|

The risk of atherosclerosis in patients with chronic kidney disease

Abstract: BackgroundChronic kidney disease (CKD) is becoming a serious health problem; the number of people with impaired renal function is rapidly rising, especially in industrialized countries. A major complication of CKD is cardiovascular disease. Accelerated atherosclerosis has been observed in early stages of renal dysfunction. The purpose of this study was to examine the relationship between the degree of renal insufficiency and both the prevalence and intensity of coronary artery disease (assessed on the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 24 publications
1
61
1
2
Order By: Relevance
“…Histological research has shown the existence of sub epidermal capillary micro-angiopathy in patients suffering from renal insufficiency, which is evidenced among other things by the presence of activation and an apoptosis of endothelial cells. This initial endothelial lesion leads to vasoconstriction followed by diffuse platelet aggregation, and the occlusion of vascular light by fibrinous thrombins [43,44].…”
Section: Endothelial Dysfunction and Crimentioning
confidence: 99%
“…Histological research has shown the existence of sub epidermal capillary micro-angiopathy in patients suffering from renal insufficiency, which is evidenced among other things by the presence of activation and an apoptosis of endothelial cells. This initial endothelial lesion leads to vasoconstriction followed by diffuse platelet aggregation, and the occlusion of vascular light by fibrinous thrombins [43,44].…”
Section: Endothelial Dysfunction and Crimentioning
confidence: 99%
“…Recently, baseline data from the National Observatory of Atherosclerosis in Nephrology (NEFRONA) (16) Study have shown that patients in early CKD stages already have a higher prevalence of atheromatous plaques than those without CKD (17,18), and as previously shown, this prevalence is even higher in advanced stages of CKD (19)(20)(21). However, it is uncertain what the velocity of atheromatosis progression in CKD is (22,23), and little is known about the predictors of plaque progression in patients with CKD.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is well established that CKD patients exhibit a disproportionate burden of atherosclerosis as compared with individuals having normal kidney function. [2][3][4][5] Furthermore, a higher prevalence of traditional risk factors for the development of atherosclerosis, such as hypertension, diabetes and hyperlipidemia, only partially accounts for the accelerated atherosclerosis in CKD patients, leading to the hypothesis that unique risk factors must be present in this population. 6,7 …”
Section: Introductionmentioning
confidence: 99%